Constitutional Democracy and Social Welfare - Mueller, Dennis C. (Quarterly Journal of Economics, 1973)
I. The constitutional stage, 61. — II. The parliamentary stage, 64. — III. The allocation of decisions between the constitutional and parliamentary stages, 70. — IV. Summary of the theory, 77. — V. Implications for democratic reforms, 79.